Representasi Matematis Siswa pada Resource-Based Learning Model berbantuan Google Classroom - Anggiana, Agus Dede; Kandaga, Thesa (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
Mathematics is a subject rich in representations, ranging from tables, diagrams, symbols, physical, to verbal. In the realm of mathematics, students are required to master all of these types of representations. To facilitate learning encompassing all of these representations, various structured materials and references are necessary. The objective of this research was to determine the extent of improvement in mathematical representation among students who received Model Resource-based Learning aided by Google Classroom. The research method employed was quasi-experimental. Sample of this study were students of grade XI in the academic year 2021/2022 at one high school in Bandung. Purposive sampling technique was used for sample selection. The research sample was selected based on available classes, ensuring that both classes had equivalent initial capabilities. One class then became the experimental group, while the other class served as the control group. The research instrument was a test of mathematical representation ability. Based on the data analysis, the improvement in mathematical representation ability among students in the experimental group was higher compared to students in the control group. It was also found that despite being provided with resources in Google Classroom, students' verbal representations were still lacking and remained the lowest type of representation besides physical representation.